CFD STUDIO: AN EDUCATIONAL SOFTWARE FOR CFD ANALYSIS - Pieritz, R. A.; Mendes, R.; Ferraz, R.; Maliska, C. R. (Revista de Engenharia Térmica, 2003)
The main goal of this paper is to demonstrate the general characteristics of the educational user-friendly CFD Studio package for CFD teaching. The package was designed for teaching 2D fluid mechanics and heat transfer process, including conduction, coupled conduction/convection, natural and forced convection, external and internal flows, among other phenomena. The finite volume methodology and its related topics can also be taught using the software. Therefore, general aspects of the three main modules, pre-processor, solver and post-processor are discussed aiming to show the generality of the tool. These modules are integrated in the application by a so-called numerical problem project which guide the student through the steps to obtain the solution. To approximate the partial differential equations the finite volume approach is employed using a fully-implicit formulation with the interpolation schemes CDS, UDS and WUDS. Mesh editing and nonorthogonal boundary-fitted mesh generation, using algebraic interpolation and elliptic equations, are important features of the package. Coupled heat transfer problems are handled using the solid-block formulation and the pressure-velocity coupling uses the SIMPLE and SIMPLEC methods with non-staggered grids. To demonstrate the capabilities two fluid flow and heat transfer problem projects are presented.